Web-based Construction Project Application Development with ReactJS, NestJS, and Agile Scrum - Muhammad Zakia Avlach; Yamasari, Yuni (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2025)
Despite the rapid advancement of web-based information technology, the construction industry still heavily relies on manual project management methods, including budget tracking, worker coordination, and design inspiration searches. PT Media Kreasi Abadi, a construction company specializing in interior design and renovation, lacks a dedicated digital platform to streamline its project management processes. To address these inefficiencies, this study aims to develop a web-based construction project management application integrating a ReactJS frontend and a NestJS backend, supported by an API-driven architecture. The system enhances collaboration among project stakeholders while improving efficiency in project tracking and management. Additionally, this research evaluates the backend's performance to ensure seamless integration with the frontend. By adopting Agile Scrum, the development process remains flexible and continuously adaptive to user needs. The findings suggest that a well-designed digital platform can significantly optimize construction project management, reduce manual errors, and enhance team coordination. Future improvements may incorporate real-time analytics and AI-driven decision-making features to further enhance system capabilities.